Implementation of Vocal Training Methods from the Stanislavski System in the Kanti Becakap - Ikhsan Satria Irianto; Tofan Gustyawan; Lusi Handayani (Gondang: Jurnal Seni dan Budaya, 2023)
This vocal training method research is an interpretation of Stanislavski's acting method. This study aims to formulate vocal training methods for actors based on the Stanislavski system. The application of this method is carried out in the Kanti Becakap (Art Community). The material object of this research is "The System" by Stanislavski which is contained in two books, An Actor's Prepares (Translation of Asrul Sani, 1980) and the book Building A Character (Translation of Gramedia Popular Library, 2008). The research method used is a qualitative method with an analytic descriptive approach. The data collection technique used was literature study and the data analysis technique used was inductive analysis. The results of the formulation of the vocal training method from the stanislavski system consist of eight training methods, Vocal Relaxation, Articulation Clarity, Vocal Volume, Musical Dialogue, Swan Neck Intonation, Possibility of Pauses, Accentuation Rules and Instinctive Rhythms. The eight formulations of the vocal training method can be divided into two exercises, namely vocal preparation and dialogue preparation.